Pulping of Diospyros Melanoxylon - Sharma, Y. K.; Rai, A. K.; Guha, S. R. D. (Indian Forester, 1975)
Laboratory scale experiments on the production of sulphate pulps from Diospyros melanoxylon are described. The wood had 16.6 percent pentosan content, 21.1 percent ligain content and 79.03 percent holocellulose. The average fibre length was 1.14 mm and average fibre diameter was 0.0175 mm. Unbleached pulps in good yield and good strength properties could be prepared. The bleaching of pulp using CEHH sequence was, however, not satisfactory. Even by applying 13 percent total chlorine the bleached pulp had mottling effect.